Two-Dimensional Vibrational Lineshapes of Amide III, II, I and A Bands in a Helical Peptide - Hayashi, Tomoyuki (2008)
An effective exciton Hamiltonian for all amide bands is used to calculate the linear absorption and photon echo spectra of a 17 residue helical peptide (YKKKH17). The cross peak bandshapes are sensitive to the inter-band couplings. Fluctuations of the local amide frequencies of the all amide fundamental and their overtone and combination states are calculated using the multipole electric field induced by environment employing the electrostatic DFT map of N-methyl acetamide. Couplings between neighboring peptide units are obtained using the anharmonic vibrational Hamiltonian of glycine dipeptide (GLDP) at the BPW91/6-31G(d,p) level. Electrostatic couplings between non-neighboring units are calculated by the fourth rank transition multipole coupling (TMC) expansion including 1/R(3) (dipole-dipole), 1/R(4) (quadrupole-dipole), and 1/R(5) (quadrupole-quadrupole and octapole-dipole) interactions.